Tutoring is a Promoter of Spirituality - Saidovna, Norova Malika (International Journal on Human-Computing Studies, 2023)
The article analyzes the issues of effective organization of tutoring activities in higher educational institutions, organization of students' free time in a new spirit, motivational, organizational and practical work.